2019
DOI: 10.1001/jamaophthalmol.2019.1947
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of New Choroidal Neovascularization in Fellow Eyes of Patients With Age-Related Macular Degeneration Treated With Intravitreal Aflibercept or Ranibizumab

Abstract: to neovascular age-related macular degeneration (nAMD) in untreated fellow eyes of patients who are treated for nAMD in 1 eye with anti-vascular endothelial growth factor agents provides important prognostic information to clinically manage patients. OBJECTIVE To investigate the association of treatment assignment (intravitreal aflibercept vs ranibizumab) and baseline characteristics with fellow eye conversion to nAMD in the VEGF (Vascular Endothelial Growth Factor) Trap-Eye: Investigation of Efficacy and Safe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 28 publications
1
23
0
1
Order By: Relevance
“…[11][12][13][14][15][16][17] Conversion in the fellow eye has been reported to occur in between 6% and 30% of patients having unilateral wet AMD for 5 years. [24][25][26] Our results reflect similar findings, with conversion rates ranging from 3.3% to 5.7% during the first 2 years of follow-up and treatment in 1 eye, to between 20.3% and 36.4% from 2 years onward ( Figure 2). Few studies have compared the frequency of intravitreal injections between initially diagnosed and fellow eyes.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…[11][12][13][14][15][16][17] Conversion in the fellow eye has been reported to occur in between 6% and 30% of patients having unilateral wet AMD for 5 years. [24][25][26] Our results reflect similar findings, with conversion rates ranging from 3.3% to 5.7% during the first 2 years of follow-up and treatment in 1 eye, to between 20.3% and 36.4% from 2 years onward ( Figure 2). Few studies have compared the frequency of intravitreal injections between initially diagnosed and fellow eyes.…”
Section: Discussionsupporting
confidence: 86%
“…24 This has been supported by more recent studies as well, showing a rate of conversion approximating 30% over the course of 5 years. 25,26 Furthermore, it has been suggested that the type of CNV presenting in the first eye could be predictive of the neovascularization patterns manifesting in the fellow eye, and response to treatment in one eye may potentially be used to predict responses to anti-VEGF therapy in the fellow eye. 27 To date, there is minimal evidence regarding the suggested frequency of screening of wet AMD in the fellow eye after unilateral diagnosis of wet AMD.…”
Section: Conversion To Wet Age-related Macular Degenerationmentioning
confidence: 99%
“…Another key problem is the influence of anti-VEGF treatment in one eye on the fellow eye that has no clinical signs of neovascularization at baseline. Post hoc analysis of some major randomized, double-masked, active-controlled, multicenter clinical trials could not reveal any consistent influence of intravitreal ranibizumab or aflibercept injections on fellow eye conversion rates (17,18). When studying bevacizumab, also, no difference was noted in the first study year (7.2% of patients treated with bevacizumab vs. 7.9% of patients treated with ranibizumab).…”
Section: The Current State Of Knowledge Regarding the Systemic Exposumentioning
confidence: 92%
“…Literature data largely vary on this topic. In clinical trials fellow eye involvement was noted at 22, 24 and 36.3% of patients by 24 months (16)(17)(18), regardless of the medication. A recent real-life evaluation reported a 32% fellow eye involvement rate at two years (19).…”
Section: The Current State Of Knowledge Regarding the Systemic Exposumentioning
confidence: 98%
See 1 more Smart Citation